Navigating ICT-Related Factors and Life Satisfaction in Older Adults: A Social Cognitive Theory Approach - Liqin Yu; Harrison Hao Yang; Dan Ma; Fulin Liu; Manyu Sun (SAGE Open)
As the world’s aging population continues to grow, leveraging technology to support healthy aging presents significant advantageous. Numerous studies have investigated the impact of ICT-related factors on the life satisfaction of older adults. However, existing research often approached these factors from a single perspective, overlooking potential threshold effects. This study addresses this gap by exploring the multifaceted determinants of ICT-related life satisfaction among older adults, incorporating the notion of threshold effects. A structured questionnaire was administered to 418 older adults residing in Wuhan, China, capturing their experiences and perceptions. Linear regression and piecewise regression model were utilized to explore both the linear and threshold effects of ICT-related factors on older adults’ life satisfaction. The findings reveal that (1) a positive attitude toward ICT, ICT use for social communication, and receiving feedback on digital skills and safety and security significantly and positively impact life satisfaction; (2) the use of ICT for learning and training was found to negatively affect older adults’ life satisfaction; and (3) attitudes toward ICT, ICT use for learning or training, digital skills feedback, and digital safety and security feedback exhibited threshold effects, suggesting that these factors significantly impact life satisfaction only up to a specific threshold. Beyond these thresholds, the effects tend to diminish or even reverse. This study offers a more comprehensive and precise understanding of the key ICT-related factors influencing older adults’ life satisfaction, along with their underlying mechanisms. Based on these findings, this study concludes by providing practical recommendations to enhance the well-being of older adults in the digital era.